The value chain in productivity of micro, small, and medium-sized enterprises (MSMEs) amid the COVID-19 - Rios Delgado, Teresa Jesús (2021)
The value chain is made up of value-added activities to transform a product or service into value creation and ranges from its production to its commercialization. Thus, the analysis of the value chain in a company allows a situational diagnosis of the capacity to generate value for the company. Therefore, it could be argued that the value chain is the cornerstone of productivity. Likewise, it is a strategic tool in the management of companies in order to achieve a competitive advantage, optimizing their resources and activities to achieve its market positioning. This essay analyzes the value chain as an opportunity in the environment and amid COVID-19. Theoretical foundations and reflections are presented that can be applied in any type of company regardless of the size it may have.